2018
DOI: 10.1002/pc.24946
|View full text |Cite
|
Sign up to set email alerts
|

Buckling strength optimization of fabrication factors of composite lattice cylinders using experimental‐statistical method (Taguchi)

Abstract: The effects of fabrication factors on the maximum buckling strength of composite lattice cylinders using experimental–statistical method are investigated. Composite lattice cylinders are fabricated using a silicone rubber mandrel, an automatic filament winding machine and autoclave. Design of experiments has been done using the Taguchi method and the orthogonal array L9 is used. The effects of four fabrication factors including “fiber tension”, “winding speed”, “cure cycle”, and “type of fiber” (Aramid, Glass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…As a result, studies on these structures have increased. Some studies have been considered two-dimensional topologies of isogrid, 10,11 anisogrid, 10,12,13 and honeycomb 4,14 cores as well as three-dimensional topologies of pyramidal, 68,1520 tetrahedral, 21,22 kagome, 23 X-type, 24,25 octet-truss, 26,27 and corrugated 9,28 cores. Furthermore, the effect of using metal 7,27,29,30 and fiber-reinforced composite (FRC) materials 1726 on the capability of carrying various loading has been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, studies on these structures have increased. Some studies have been considered two-dimensional topologies of isogrid, 10,11 anisogrid, 10,12,13 and honeycomb 4,14 cores as well as three-dimensional topologies of pyramidal, 68,1520 tetrahedral, 21,22 kagome, 23 X-type, 24,25 octet-truss, 26,27 and corrugated 9,28 cores. Furthermore, the effect of using metal 7,27,29,30 and fiber-reinforced composite (FRC) materials 1726 on the capability of carrying various loading has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of using metal 7,27,29,30 and fiber-reinforced composite (FRC) materials 1726 on the capability of carrying various loading has been investigated. Examples of these loadings are axial compression, 1013 in-plane compression, 17,19,25,28,30 and out-of-plane compression 4,16,2125,27,30 loads as well as on three-point bending, 23,28 torsion, 18 shear loading, 16,21,2528,30 and impact loading. 57,14 Researches have shown that the use of carbon-FRC in comparison with metal materials, in addition to improving the mechanical behavior of structures, can lead to high fuel efficiency in naval ships and submarine propellers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, studies on these structures have increased. Some studies have been considered two-dimensional topologies of isogrid, 10,11 anisogrid 10,12,13 and honeycomb 4,14 cores as well as three-dimensional topologies of pyramidal, 68,1520 tetrahedral, 21,22 kagome, 23 X-type, 24,25 octet-truss 26,27 and corrugated 9,28 cores. Furthermore, the effect of using metal 5,7,27,29 and fiber reinforced composite (FRC) materials 1726 on the capability of carrying various loading has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of using metal 5,7,27,29 and fiber reinforced composite (FRC) materials 1726 on the capability of carrying various loading has been investigated. Examples of these loadings are axial compression, 1013 in-plane compression, 17,19,25,28,29 and out-of-plane compression 4,16,2125,27,29 loads as well as on three-point bending, 23,28 torsion, 18 shear loading, 16,21,2529 and impact loading. 57,14 Researches have shown that the use of carbon-FRC in comparison with metal materials, in addition to improving the mechanical behavior of structures, can lead to high fuel efficiency in naval ships and submarine propellers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation